Determinants of Indonesia Government Bonds Yield Period 2019-2022 - Husein, Destyanah; Endri, Endri (Green Publisher Indonesia, 2024)
This research seeks to examine how the yields of Indonesian government bonds are influenced by various factors, including the BI interest rate, inflation, foreign exchange reserves, IHSG, and exchange rates. The investigation utilizes monthly time series data spanning from 2019 to 2022, focusing on the benchmark series of 10-year SUN. Data analysis is carried out using Eviews 13, and the GARCH-M (1,1) analytical method is employed. The research findings reveal that the BI interest rate has a notably positive and significant effect on bond yields. In contrast, inflation does not exhibit a significant impact on bond yields. Foreign exchange reserves are found to have a considerable negative impact on bond yields. IHSG, on the other hand, does not demonstrate a significant influence on bond yields. Lastly, exchange rates are identified as having a meaningful positive impact on bond yields.